ANALYSIS OF THE EFFECT OF BILGE KEEL ON THE ROLLING MOTION OF RO-RO FERRY SHIP USING THE STRIP-THEORY METHOD - Ramli Firdaus Kusnadi; Puranggo Ganjar Widityo; Ahmad Yasim; Baharuddin Ali (ROTOR, 2023)
Ships are a mode of transportation that is often used by the community as a link between the islands. People generally use the ferry as a mode of crossing in addition to the economical price but also comfort is still preferred. But in recent years, researchers have often heard cases of shipwrecks. Especially ship crossing accidents caused by overturned ships. Based on this, prevention is needed to reduce the number of ship accidents in the future. One of the keys that can be taken is to improve the technical analysis before the ship is designed. One such analysis related to the ship is seakeeping ship. The method used in this study is to use strip – theory method through OSM program. This method is one of the commonly used methods because it calculates the 3D model into 2D. The results showed the effect of the use of Bilge keel on the ferry Ro-Ro tested with conditions x0, x1, x2, and x3 on the condition of the stationary ship with a wave height of 1,5 m and heading 90o. The addition of Bilge keel is able to reduce the resonance of roll motion up to 58% in conditions of variation x1, 61% in variation x2, and 67% in conditions of variation x2. Therefore, the installation of bilge keel has a significant effect on the rolling of ferry Ro-Ro.